Study of Concrete: Quality and Economic - Djaelani, Mohammad; Judiono, Judiono; Darmawan, Didit; Amri, Muhammad Wayassirli (Metromedia, 2022)
Concrete has been widely used as a building material. In general, Portland cement, water, and aggregate are the basic ingredients for making concrete along with various additives to strengthen concrete. The strength, durability, and other properties of concrete depend on the properties of these basic materials. This paper reviews the types of concrete, concrete quality parameters, advantages and disadvantages of concrete and general properties of concrete.